Digenic heterozygous mutations of KCNH2 and SCN5A induced young and early‐onset long QT syndrome and sinoatrial node dysfunction. Issue 1 (9th November 2021) - Yang, Zhe; Ma, Yuting; Huang, Jiana; Xian, Jianzhong; Huang, Yin; Wu, Linbo; Zhu, WenLiang; Wang, Feng; Chen, Liang; Lin, Xiufang; Lin, Yubi
Abstract: Introduction: Long QT syndrome (LQTS) is a life‐threatening inherited channelopathy, and prolonged QT intervals easily trigger malignant arrhythmias, especially torsades de pointes and ventricular fibrillation. Materials and methods: The proband with overlapped phenotypes of LQTS and sinoatrial node dysfunction underwent some necessary examinations, including echocardiography, electrocardiogram (ECG), and Holter monitoring. Next, whole‐exome sequencing was performed, and candidate genes were validated by Sanger sequencing. RNA secondary structure and protein physical‐chemical parameter analyses were used to predict the possible structural change of the proteins induced by the mutations. Results: We identified the digenic heterozygous mutations of KCNH2 p.307_308del (NM_001204798, c.921_923del) and SCN5A p.R1865H (NM_001160160, c.G5594A) in the female and young proband (II: 1) of LQTS and ventricular fibrillation with repeat syncope at rest. Subsequently, she occurred with obvious sinus arrest with persistent ventricular pacing of implantable cardioverter‐defibrillator. The heterozygous SCN5Ap.R1865H was carried by her father and sister but not carried by I:2. II:1 carried with KCNH2 p.307_308del as a de novo mutation, but not existed in other family members. RNA secondary structure of KCNH2 p.307_308del showed a false regional double helix, and its amino acids' hydrophobicity was significantly weakened. For the Nav 1.5 protein property, SCN5A p.R1865H slightly increased the molecular weight and aliphatic index but reduced the instability index. Conclusions: The digenic heterozygous KCNH2 and SCN5A mutations were associated with young early‐onset long QT syndrome and sinoatrial node dysfunction.